Gas–particle phase partitioning and particle size distribution of chlorinated and brominated polycyclic aromatic hydrocarbons in haze. (December 2017) - Jin, Rong; Zheng, Minghui; Yang, Hongbo; Yang, Lili; Wu, Xiaolin; Xu, Yang; Liu, Guorui
Abstract: Chlorinated and brominated polycyclic aromatic hydrocarbons (Cl/Br-PAHs) are emerging semi-volatile organic pollutants in haze-associated particulate matter (PM). Their gas–particle phase partitioning and distribution among PM fractions have not been clarified. Clarification would increase understanding of atmospheric behavior and health risks of Cl/Br-PAHs. In this study, samples of the gas phase and 4 PM phases (aerodynamic diameters ( d ae ) > 10 μm, 2.5–10 μm, 1.0–2.5 μm, and <1.0 μm) were collected simultaneously during haze events in Beijing and analyzed. Normalized histogram distribution indicated that the Cl/Br-PAHs tended to adhere to fine particles. Over 80% of the Cl-PAHs and 70% of the Br-PAHs were associated with fine PM ( d ae < 2.5 μm). The gas–particle phase partitioning and PM distribution of Cl/Br-PAHs when heating of buildings was required, which was associated with haze events, were obviously different from those when heating was not required. The relationship between the logarithmic geometric mean diameters of the Cl/Br-PAH congeners and reciprocal of the temperature (1/ T ) suggested that low air temperatures during the heating period could lead to high proportions of Cl/Br-PAHs in the fine particles. Increased coal burning during the heating period also contributed to high Cl/Br-PAH loads in the fine particles. Graphical abstract: Highlights: Particle size distributions of Cl/Br-PAHs in the haze were firstly reported. Cl/Br-PAHs were mainly bonded with fine particles ( d ae < 2.5 μm). With the decrease of temperature, Cl/Br-PAHs tended to adhere to fine particles. Coal burning contributed to the increasing loads of Cl/Br-PAHs in fine particles. Abstract : The gas-particle phase partitioning and particle size distribution of both chlorinated and brominated PAHs in haze were firstly evaluated.